Traumatic haemopneumothorax and 'whole-body' subcutaneous emphysema: successful use of a small-bore chest drain. (2nd December 2016) - Hardy, Benjamin; Sunderland, Nicholas; Perera, Mevan; Channing, Kathryn
Abstract : A 56-year-old man presented having had two falls at home. He had a background of multiple sclerosis. After his second fall, during which he had fallen onto the toilet injuring his right chest, he was brought into the emergency department reporting pleuritic chest discomfort. Immediately evident was extensive swelling from his forehead to his thighs, which on palpation was found to be subcutaneous emphysema. A chest X-ray showed a large right-sided pneumothorax for which a chest drain was inserted. A CT revealed extensive surgical emphysema, pneumomediastinum, pneumoperitoneum and gas within the spinal canal. It also showed right-sided rib fractures and associated haemothorax. He was managed conservatively with a 12-French (F), small-bore, chest drain and made a complete recovery without complication. This case challenges the widely held, but poorly evidenced, opinion that traumatic haemopneumothorax needs to be managed with a large-bore surgical chest drain.